Terjemahan Takarir Dialog Berbahasa Arab dalam Film Ketika Cinta Bertasbih 1 - Ahmad Marzuq; Mohamad Sarip (Program Studi Magister Linguistik Terapan UNJ, 2022)
The entertainment industry, including foreign language films, can be an interesting object of study in translation studies. In foreign language films there are translations in various languages, according to the object of the audience. The film When Cinta Bertasbiqh I (KCB I) is one of the films in which there are dialogues in foreign languages, in this case Arabic. The subtitles of this film (subtitles) can be researched by being oriented towards the source language and the target language. This can be seen from some of the dialogues in the KCB I film which features various Arabic fusha and Egyptian 'amiyah. Therefore, this study aims to describe and classify the variety of sentences in the dialogues contained in the KCB I film along with their translations. From the results of the analysis it was found that the fusha variety is more often used in formal conditions, while the Egyptian 'amiyah variety is widely used in daily dialogue. The translations presented in the subtitles of the KCB I film tend to prioritize equivalence of meaning and are more oriented to the target language, this allegedly aims to provide comfort to the audience.